Servant Leadership towards Teachers’ Perceived Organizational Support - Utami, Sri; Marisa, Cindy; Satrianta, Hengki (Candradimuka: Journal of Education, 2025)
Perceived organizational support will encourage teachers to work optimally. Teachers need to have a feeling that the organization, in this case the school, provides total support. However, serving leadership from the principal is also needed to produce that. This study aims to determine the effect of serving leadership on perceived organizational support. This study involved 148 private high school teachers in Depok City who were estimated through the slovin formula at the 5% significance level. Data were collected through serving leadership and perceived organizational support scale techniques. Data were analyzed descriptively and inferentially. Hypotheses were tested using linear regression tests. Results showed that serving leadership has a significant effect on perceived organizational support. In-depth exploration of the indicators that dominate this effect is needed.